Student perception of socio-emotional profiles of student actors in school violence - Gómez Villalpando, Armando; González García, Javier (Emerging Trends in Education, 2026)
This study explores university students’ perceptions of the socio-emotional profiles of school bullying actors (perpetrators, victims, and bystanders). Using a questionnaire built from a selective literature review on bullying and socio-emotional competences, and completed by 89 students, we computed response frequencies and conducted an interpretive analysis of emergent patterns. For perpetrators, the most cited triad—lack of guilt, low empathy, and anger reactivity—forms a “cold–hot” profile that enables repeated harm. For victims, emotional distress, difficulty seeking help, and social withdrawal predominate, an “affect–agency–bond” sequence that entrenches vulnerability. For bystanders, ambivalence about intervening, diffusion of responsibility (“not my problem”), and group conformity stabilize passivity.